Physical oceanography during RV MARIA S. MERIAN cruise MSM134 - Emil Michels; Lukas Dirksen; Hendrik Grotheer; Malte Höhn; Jana Chiara Massing; Ricarda Meineke; Clemens Röttgen; Daniel Smrzka; Karin A F Zonneveld (PANGAEA, 2025)
Physical oceanography data was acquired by a ship-based Seabird SBE911plus CTD-Rosette system onboard RV MARIA S. MERIAN during research cruise MSM134. The CTD system is comprised of a Seabird SBE911plus including dual respectively redundant sensor and pump packages. The SBE11plus Deck Unit remains on board in a laboratory and supplies on one hand power to the SBE9plus underwater unit, on the other hand data telemetry between the SBE9plus and a measurement PC. The SBE9plus underwater unit itself holds a pressure sensor and is interfacing with dual SEB3 temperature, SBE4 conductivity and SBE43 oxygen sensors, as well as two SBE5 pumps to provide a pumped water supply past each sensor. The system also carries an optical FLNTU sensor to measure a combination of back-scattering, turbidity, and chlorophyll-a. To quantify the photo-synthetically active radiation a PAR sensor is installed as well.